2019
DOI: 10.1186/s12872-019-1143-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased urinary adiponectin level is associated with contrast-induced nephropathy in patients undergoing elective percutaneous coronary intervention

Abstract: Background Contrast-induced nephropathy (CIN) is one of major and serious complications in patients undergoing percutaneous coronary intervention (PCI). It is unknown whether increased urinary adiponectin (UAPN), a sensitive marker for early renal function impairment, is associated with an increased risk of CIN. Therefore, we prospectively investigate the association of UAPN with CIN. Methods We prospectively enrolled 208 patients who were undergoing elective PCI. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Previous studies have demonstrated that the incidence of CIN uctuates from 6-22% in patients undergoing primary PCI [1][2][3][4] , and in our study, the incidence of CIN in the placebo group was more than 20%. Although the mechanism of CIN is not fully understood, it is believed that this complication is closely related to renal ischemic injury and the direct renal tubular cytotoxicity of contrast medium 15 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies have demonstrated that the incidence of CIN uctuates from 6-22% in patients undergoing primary PCI [1][2][3][4] , and in our study, the incidence of CIN in the placebo group was more than 20%. Although the mechanism of CIN is not fully understood, it is believed that this complication is closely related to renal ischemic injury and the direct renal tubular cytotoxicity of contrast medium 15 .…”
Section: Discussionsupporting
confidence: 58%
“…CIN is associated with prolonged hospitalization, increased risk of adverse cardiovascular events, as well as short-and long-term mortality [1][2] . Some studies are exploring effective prevention for CIN [3][4][5] . To assess the efficacy of nicorandil for CIN prevention in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary PCI, we analyzed a multi-center prospective randomized controlled trial, which explored the effects of nicorandil administration on infarct size in patients with STEMI treated with PPCI (primary PCI) 6 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 In patients undergoing PCI, contrast-induced nephropathy (CIN) has become a serious complication and it is closely related to clinical adverse events, such as an increased incidence of renal failure and increased short- and long-term mortality rates. 3 , 4 CIN refers to an increase in serum creatinine levels by 25% or an increase in the absolute value by more than 44.2 μmol/L after application of a contrast agent. 5 CIN has become a common cause of hospital-acquired kidney damage.…”
Section: Introductionmentioning
confidence: 99%
“…1 Regardless of procedural success, CIN is associated with prolonged hospital stay and clinical adverse events, such as an increased incidence of renal failure and increased short and long-term mortality rates. 2,3 Moreover, patients with acute coronary syndrome (ACS) have a high incidence of CIN (3 times higher than that in other groups). 4,5 Therefore, the identification of safe and effective methods to prevent CIN is particularly important in this population.…”
Section: Introductionmentioning
confidence: 99%